A system dynamics framework for the assessment of resource and energy efficiency in iron and steel plants. (10th December 2020) - Norbert, Raphaël; Kim, Junbeum; Griffay, Gérard
Abstract: The iron and steel industry is one of the most energy-intensive industrial sectors, which makes a significant worldwide contribution to resource and energy consumption, as well as to carbon dioxide emissions. Up to date, much effort has been put into increasing the global efficiency of the internal production processes. Still, the potential for improvements tends to be more and more limited at the level of a steel plant. That is why many methodologies and tools have been, and are still being, developed to study industrial symbiosis in such areas, but most of them propose a static view. Indeed, typically integrated iron and steel plants have a significant role to play in industrial symbiosis. However, the question remains: how to evaluate the economic and environmental benefits or impacts of industrial symbiosis on such industrial sites? Therefore, the objective of this study is to propose a new methodology based on the concepts of system dynamics while providing a systematic approach for assessing these industrial symbiosis performances. This approach relies on a dynamic model resulting from the combination of a physicochemical sub-model and a system dynamics sub-model. This model built and applied a whole steel plant is fed by all resource and energy flows (i.e., not limited to one process but considering all processes). This dynamic model is tested and validated over a two-year simulation period using different statistical tests that show its relevance to industrial symbiosis scenario simulations involving complex systems fed by variable resource and energy flows. This proposal can thus be used to simulate the substitution or exchange of any material and energy streams of steel plants while allowing the economic and environmental benefits or impacts to be quantified from any industrial symbiosis configuration. Graphical abstract: Image 1